The Greater Ontario to be developed by the Bruce Mines & Algoma Railway [electronic resource] : which is the western Ontario route to Hudson Bay. ([Ontario? : s.n., 1901)
Tables. Date from text. Caption title: The great claybelt of Northern Ontario, containing over 15,000,000 acres. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44